Nb3Cl8: a prototypical layered Mott-Hubbard insulator - Sergii Grytsiuk; Mikhail I. Katsnelson; Erik G.C.P. van Loon; Malte Rösner (npj Quantum Materials, 2024)
Abstract Despite its simplicity and relevance for the description of electronic correlations in solids, the Hubbard model is seldom inarguably realized in real materials. Here, we show that monolayer Nb3Cl8 is an ideal candidate to be described within a single-orbital Hubbard model, constructed within a “molecular” rather than atomic basis set using ab initio constrained random phase approximation calculations. We provide the necessary ingredients to connect experimental reality with ab initio material descriptions and correlated electron theory, which clarifies that monolayer Nb3Cl8 is a Mott insulator with a gap of about 1.4 to 2.0 eV depending on its dielectric environment. Comparisons to an atomistic three-orbital model show that the single-molecular-orbital description is adequate and reliable. We further comment on the electronic and magnetic structure of the compound and show that the Mott insulating state survives in the low-temperature bulk phases of the material featuring distinct experimentally verifiable characteristics.